DENTAL ANXIETY AMONG CHILDREN OF AGE BETWEEN 5 TO 10 YEARS VISITING A TEACHING DENTAL HOSPITAL IN ISLAMABAD, PAKISTAN - Raja, Gulrez Hanif; Malik, Faisal Shafiq; Bashir, Ulfat; ullah, Atta (Journal of Ayub Medical College Abbottabad, 2015)
Background: The assessment of dental anxiety among children will aid in dealing with management issues related to dental treatment. There is no study available from Pakistan on dental anxiety in children. The aim of this study was to assess the prevalence of dental anxiety in children attending a teaching dental hospital in Islamabad, Pakistan. Methods: A cross-sectional study was conducted on 252 children aged between 5-10 years attending a dental clinic in a dental hospital in Islamabad, Pakistan. Dental anxiety was assessed by using the Faces Version of the Modified Child Dental Anxiety Scale. This scale uses faces as pictograms to indicate the levels of dental anxiety making it easier for children to answer the questionnaire. Results: A total of 252 children were observed for assessment of dental anxiety having mean age of 7.88±1.55 years with 123 (48.8%) males and 129 (51.2%) females. Out of these children 150 (59.5%) had previously visited a dentist and 102 (40.5%) had no experience with a dentist before; 38% (95/252) of children had moderate and severe dental anxiety. Dental anxiety decreased significantly with age (p=0.0003). The difference in anxiety levels was not statistically significant between males and females and in different socio-economic status. Conclusion: This study has highlighted dental anxiety as a potential public health concern regarding children in Pakistan. Assessment of dental anxiety is a useful way to identify anxious dental patients.